Inference-making instructions in efl teachers guides of grades eleven and twelve in Oman: a content analysis - Al Jahwari, Yahya Sulaiman; Sheikh Ahmad, Ismail (Impact Journals, 2021)
This research is part of a larger study exploring the implementation of inference-making skill in reading comprehension in the Omani educational context. This part of the study was designed to investigate the provided instructions related to inference-making as presented in post-basic English language Teachers' Guides (TGs). In order to achieve this aim, a content analysis tool was developed which comprised of three parts. The first part is devoted to exploring the general information about inferences that are provided in TGs. The second part is about inference strategies that are provided by TGs. The third part concerns about the techniques and instructions that are provided by TGs to develop students‘ inference-making ability. The sample of this study was TGs of grades eleven and twelve in the post-basic education system. The results of the study showed that TGs did not provide an explicit definition of inference-making skill and how it should be implemented. Also, it revealed the absence of explicit inference-making strategies such as Question-answer relationships (QAR), Key Words, Infer, and Support (KIS). On the other hand, as a positive aspect, there are several inference instructions or techniques are included in Teachers‘ Guides of both grades.